War sermons - Teulié, Gilles; Lux-Sterritt, Laurence (Cambridge Scholars, 2009)
This collection of essays ponders upon the intricate relations between the military and the spiritual from the Middle Ages to the present day. In order to analyse human attitudes towards conflicts, it is necessary to dwell upon the nebulous area where the religious and political spheres interweave so tightly that they become virtually impossible to distinguish. Indeed, despite remaining the responsibility of the state, the political decision to go to war depends heavily on some spiritual unde ...